Jawabanmu

2014-03-03T19:59:19+07:00
Fx=ax+b
f(-2)=a(-2)+b
14=-2a+b.....(1)
f(3)=a(3)+b
-1=3a+b........(2)

-2a+b=14
3a+b=-1
------------ -
-5a=15
a=15/-5
a= -3

14=-2(-3) +b
14= 6+b
b= 14-6
b= 8
2014-03-03T20:01:40+07:00
Jadi, substitusikan f(-2) =14, menjadi,
x= -2, -----> 14= a(-2) + b
                  14= -2a + b    (persamaan 1)
substitusi lgi, f(3) = -1, menjadi,
x=3, --------> -1= a (3) + b
                   -1= 3a + b (persamaan 2)

eliminasi persamaan ke1 dan ke 2
14 = -2a + b
-1 = 3a + b
____________ -
15 = -5a
-3 = a

masukkan kepersamaan persamaan 1
14 = -2(-3) +b
14 = 6 + b
14-6 = b
b= 8
semoga membantu :)